Preaching and Christianization: reading the sermons of John Chrysostom - Cook, J (2016)
The rise of Late Antiquity as a separate discipline, with its focus on social history, has meant that the vast homiletic corpus of John Chrysostom has received renewed attention as a source for the wider cultural and historical context within which his sermons were preached. Recent studies have demonstrated the exciting potential his sermons have to shed light on aspects of daily life, popular attitudes and practices of lay piety. In short, Chrysostom's sermons have been recognised as a valuable source for the study of 'popular Christianity' and the extent of Christianization at the end of the fourth century. This thesis, however, will question the validity of some recent conclusions drawn from Chrysostom's sermons regarding the state of popular Christianity. A narrative has been developed in which Chrysostom is often seen as at odds with the congregations to whom he preached. On this view, the Christianity of élites such as Chrysostom had made little inroads into popular thought beyond the fairly superficial, and congregations were still living with older, more culturally traditional views about religious beliefs which preachers were doing their utmost to overcome. It is the argument of this thesis that such a portrayal is based on a misreading of Chrysostom’s sermons, and which fails to explain satisfactorily the apparent popularity that Chrysostom enjoyed as a preacher. What this thesis sets out to do, therefore, is to reassess how we read Chrysostom's sermons, with a particular focus on the harsh condemnatory language which permeated his preaching, and on which the image of the contrary congregation is largely based. To do this, this thesis sets out to recover a neglected portrayal of Chrysostom as a pastor and preaching as a pastoral and liturgical activity, through an exploration of four different but overlapping aspects of the socio-historical context within which his preaching was set. A consideration of the scholastic, therapeutic, prophetic and liturgical nature of his preaching will shed light on the pastoral relationship between the preacher and his congregation and will, significantly, provide a backdrop against which his condemnatory language can be explained and understood. It will become clear that his use of condemnatory language says more about how he understood his role as preacher than about the extent of Christianization in late-antique society. Through focussing on the issues of the social composition of the congregation and the level of commitment to (Chrysostom's) Christianity, it will be argued that sermon texts are in their nature resistant to being used as sources for this kind of social history. Despite this, however, glimpses will also emerge of a very different picture of late-antique Christianity, in which Chrysostom's congregation are rather more willing to listen and learn from their preacher than is often assumed.